Mechanistic studies of the molybdenum-catalyzed asymmetric alkylation reaction - Hughes, David L. (National Academy of Sciences, 2004)
Enantiomerically enriched, deuterated branched carbonates (Z)-(S)-PhCH(OCO(2)Me)-CH = CHD (1-D), (Z)-(R)-PhCH(OCO(2)Me)CH = CHD (2-D), and linear carbonate (E)-(S)-PhCH = CHCHD(OCO(2)Me) (3-D) were used as probes in the Mo-catalyzed asymmetric allylic alkylation with sodium dimethyl malonate, catalyzed by ligand-complex 11 derived from the mixed benzamide/picolinamide of (S,S)-transdiaminocyclohexane and (norbornadiene)Mo(CO)(4). The results of these studies, along with x-ray crystallography and solution NMR structural analysis of the π-allyl intermediate, conclusively established the reaction proceeded by a retention–retention pathway. This mechanism contrasts with that defined for Pd-catalyzed allylic alkylations, which proceed by an inversion–inversion pathway. A proposed rationale for the retention pathway for nucleophilic substitution involves CO-coordination to form a tri-CO intermediate, followed by complexation with the anion of dimethyl malonate to produce a seven-coordinate intermediate, which reductively eliminates to afford product with retention of configuration.